MENINGKATKAN KOMPETENSI GURU DALAM MENERAPKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA PROSES PEMBELAJARAN MELALUI IN HOUSE TRAINING DI SMP NEGERI 9 BOGOR - Akhmad Bukhori (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
IMPROVING TEACHER COMPETENCE IN APPLYING INFORMATION AND COMMUNICATION TECHNOLOGY IN THE LEARNING PROCESS THROUGH IN HOUSE TRAINING IN JUNIOR HIGH SCHOOLS (SMP NEGERI 9 BOGOR)Based on the results of observing the ability to use computers for 42 teachers at SMP Negeri 9 Bogor, the results obtained were that 17 teachers were still not able to use computers, 25 teachers were able to use computers. Departing from these problems, the implementation of In-House Training is to help improve teachers' abilities in the use of Information and Communication Technology (ICT). In House Training (IHT) is needed to improve the ability of these teachers. The research was conducted using the School Action Research method. The results of the study show that teacher competence in applying ICT through In House Training can actually increase teacher interest, enthusiasm, concentration, and activeness in the learning process. In addition, there has also been an increase in teacher competence in applying ICT in the form of an increase in average scores and an increase in individual and classical abilities for teachers at SMP Negeri 9 Bogor. Thus, based on the exposure of this research, it can be concluded: 1. the implementation of In House Training can increase the competence of teachers in applying ICT, 2. the implementation of In House Training makes teachers not bored and bored instead they feel excited so that their learning activities also increase, this is proven to aspects of the seriousness of teachers in participating in IHT activities there was an increase in the percentage of teachers from cycle I to cycle II, namely 78% in cycle I to 84% in cycle II, and 3. the large increase in ability that can be achieved through In House Training activities in applying ICT is in initial conditions have an average value achieved only 33.35. When the In-House Training was carried out, the average teacher's ability increased to 48.94 in cycle 1 and 61.12 in cycle II.